Unpredicted Sudden Death due to Recurrent Infratentorial Hemangiopericytoma Presenting as Massive Intratumoral Hemorrhage: A Case Report and Review of the Literature - Tanaka, Toshihide (Case Rep Neurol Med, 2014)
Unpredicted sudden death arising from hemangiopericytoma with massive intracranial hemorrhage is quite rare. We encountered a patient with recurrent infratentorial hemangiopericytoma presenting as life-threatening massive intracerebral hemorrhage. A 43-year-old man who had undergone craniotomy for total resection of an infratentorial hemangiopericytoma 17 months earlier presented with morning headache and generalized convulsions. Computed tomography revealed a massive hematoma in the right infratentorial region causing tonsillar herniation and emergency surgery was performed to evacuate the hematoma. Histological findings revealed hemangiopericytoma with hemorrhage. Neurological status remained unimproved and brain death was confirmed postoperatively. Hemangiopericytoma presenting as massive hemorrhage is quite rare. Since the risk of life-threatening massive hemorrhage should be considered, careful postoperative long-term follow-up is very important to identify tumor recurrences, particularly in the posterior cranial fossa, even if the tumor is completely removed.